Printing Effects of Different Natural Colourants on Cotton Fabric - Rana, Md. Bipul; Hasan, Md. Zahid; Islam, Md. Azharul; Rokonuzzaman, Md; Khandaker, Shahjalal; Bashar, M. Mahbubul (Textile & leather review (Online), 2022)
Natural colourants were widely employed in the ancient world to colour cotton garments. With the revolution of synthetic dyes, natural dyes have lost their position in respect of some performance. However, nowadays the demand for sustainable and eco-friendly products is increasing worldwide due to the awareness of ecological balance. The purpose of this study is to utilize natural colourants in printing on cotton fabric. In this regard, the colourants were extracted from myrobalan fruit, pomegranate peel and catechu, which were eventually applied to the fabric by screen printing technique. The print paste was prepared with carboxymethyl cellulose (CMC) as a natural thickener and polyvinyl alcohol (PVA) as a synthetic thickener. The stability of the print paste was studied with respect to time elapse by viscosity measurement. The depth of shade and colour fastness of the printed fabric were measured. K/S value was evaluated with respect to the stability of print paste. The viscosity was changed slightly in both the CMC and PVA thickener with respect to the stability of the print paste. The washing fastness grades for colour staining wash ranged from 4 to 5, rubbing fastness grades of dry rubbing also ranged from 4 to 5, wet rubbing fastness was 3/4 to 4/5 as well as perspiration fastness grades in alkaline, and in acidic it was 3/4 to 5. Thus, myrobalan fruit, pomegranate peel and catechu have shown excellent performance in printing on cotton textiles, which could be an alternative to the synthetic counterpart.